Q: What is the answer to the equation -10 equals 6x - 16?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

you just only need the first 2 parts of the equation! 6x-10=10x so you have to minus 6x each side: so 6x-6x-10=10x-6x, so it turns to -10=4x. Then you have to divide -10 by 4. so -10/4=-2.5 so x is -2.5.

6x - 12 = 16 is a linear equation in one variable(here x). And the value of x which satisfies the equation is the solution. Let us find the value of x: 6x - 12 = 16 Adding 12 to both sides, we get 6x - 12 + 12 = 16 + 12 6x = 28 Dividing both sides by 6, we get x = 28/6 = 14/3 So, the solution of the equation is x = 14/3.

From first equation y = 3x + 5. Substitute this in second equation 2(3x + 5) = 6x + 10 This proves that 6x + 10 = 6x + 10 which is not helpful! I suppose possible solutions would be x = 0, y = 5 or x = 1, y = 8 etc etc Are you sure of your two equations, please?

x=10 For the equation -9 - 6x +7x = 1 First, add nine to both sides to get all of the x's on one side -9 - 6x + 7x = 1 +9 +9 -6x +7x = 10 Then, combine like terms on the left side -6x+7x=10 x=10

Equals anything... x is a variable. If that equation was set equal to zero then you could solve for x, but that is not what you have asked.

Related questions

If 6x + 10 = 11x , then x=2.

you just only need the first 2 parts of the equation! 6x-10=10x so you have to minus 6x each side: so 6x-6x-10=10x-6x, so it turns to -10=4x. Then you have to divide -10 by 4. so -10/4=-2.5 so x is -2.5.

6x-14x+16=27+11 answer: 4

5x6 = 30 -10 = 20.

x2 + 6x = 16=> x2 + 6x - 16 = 0=> x2 + 8x -2x - 16 = 0=> (x+8)(x-2) = 0=> x = -8 or x = 2So, the solutions of the quadratic equation x2 + 6x = 16 are -8 and 2.

x=-8

{-1,7}

6x - 12 = 16 is a linear equation in one variable(here x). And the value of x which satisfies the equation is the solution. Let us find the value of x: 6x - 12 = 16 Adding 12 to both sides, we get 6x - 12 + 12 = 16 + 12 6x = 28 Dividing both sides by 6, we get x = 28/6 = 14/3 So, the solution of the equation is x = 14/3.

From first equation y = 3x + 5. Substitute this in second equation 2(3x + 5) = 6x + 10 This proves that 6x + 10 = 6x + 10 which is not helpful! I suppose possible solutions would be x = 0, y = 5 or x = 1, y = 8 etc etc Are you sure of your two equations, please?

x=10 For the equation -9 - 6x +7x = 1 First, add nine to both sides to get all of the x's on one side -9 - 6x + 7x = 1 +9 +9 -6x +7x = 10 Then, combine like terms on the left side -6x+7x=10 x=10

Equals anything... x is a variable. If that equation was set equal to zero then you could solve for x, but that is not what you have asked.

x=10